Aristotle in China : language, categories, and translation - Wardy, Robert (Needham Research Institute studies ;, 2000)
In an exploration of the relation between language and thought, the author analyses linguistic relativism with reference to a Chinese translation of Aristotle's Categories. In so doing he addresses some key questions relating to philosophy, language and translation. His findings will fascinate scholars in the field and related disciplines.